2023
DOI: 10.1097/olq.0000000000001830
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus positivity at three anatomical sites among transgender women in Central Brazil

Abstract: Background: Transgender women (TGW) are susceptible to the acquisition of sexually transmitted infections (STIs), including human papillomavirus (HPV). Nonetheless, the exact data for this population are scarce. We estimated HPV positivity at the anal, genital, and oral sites among TGW and also identified the related characteristics and behaviors that could be risk factors for HPV infection in a sample of TGW in Brazil. Furthermore, we characterized the site-specific HPV genotypes among those who were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 27 A Brazilian study of 268 transgender women reported a study prevalence to be 77% in anal, 34% in genital and 11% oral specimens. 28 Studies from both The Netherlands and Thailand estimate a 20% prevalence of neovaginal high-risk HPV, though these two studies had a high proportion of invalid HPV results, suggesting the true prevalence may be higher. 29 30 The oncogenic potential of persistent high-risk HPV infection in the vagina of TWNB is poorly understood and current guidelines do not recommend screening for this population.…”
Section: Introductionmentioning
confidence: 99%
“… 27 A Brazilian study of 268 transgender women reported a study prevalence to be 77% in anal, 34% in genital and 11% oral specimens. 28 Studies from both The Netherlands and Thailand estimate a 20% prevalence of neovaginal high-risk HPV, though these two studies had a high proportion of invalid HPV results, suggesting the true prevalence may be higher. 29 30 The oncogenic potential of persistent high-risk HPV infection in the vagina of TWNB is poorly understood and current guidelines do not recommend screening for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, new evidence has suggested that HPV52 and 58 may be of particular concern to oral health professionals and oral epidemiologists [ 22 , 23 , 24 ]. Although most of the research into these high-risk strains has focused on cervical infections, there is evidence that these strains may be involved in the oncogenesis and transformation of oral infections and may mediate or modulate oral carcinogenesis [ 25 , 26 , 27 ]. Although previous studies at this institution have explored the high-risk oral prevalence of HPV strains 16 and 18 among children and adults, only one study to date has assessed additional high-risk strains, such as HPV31, 33, and 35, and no study to date has evaluated the presence of HPV52 and HPV58 among this patient population [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%